THE ROLE OF INTERNAL CORPORATE PROGRAM OF TRAINING OF THE PERSONNEL IN THE COMPANY DEVELOPMENT - E. Kashtanova (Вестник университета)
Presents arguments justifying the role and importance of corporate training in the General concept of staff development in large domestic companies. Dana is a modern interpretation of an internal training program, linking it with the management of the entire company and its performance. Reviewed and systemized the purpose of the internal program of training staff grouped the forms and methods of training, describes the main stages of formation of internal corporate program of training of the personnel.